BRD4‐PRC2 represses transcription of T‐helper 2‐specific negative regulators during T‐cell differentiation. (31st January 2023) - Zhao, Li; Wang, Yiqi; Jaganathan, Anbalagan; Sun, Yifei; Ma, Ning; Li, Ning; Han, Xinye; Sun, Xueying; Yi, Huanfa; Fu, Shibo; Han, Fangbin; Li, Xue; et al.
Abstract: BRD4 is a well‐recognized transcriptional activator, but how it regulates gene transcriptional repression in a cell type‐specific manner has remained elusive. In this study, we report that BRD4 works with Polycomb repressive complex 2 (PRC2) to repress transcriptional expression of the T‐helper 2 (Th2)‐negative regulators Foxp3 and E3‐ubiqutin ligase Fbxw7 during lineage‐specific differentiation of Th2 cells from mouse primary naïve CD4 + T cells. Brd4 binds to the lysine‐acetylated‐EED subunit of the PRC2 complex via its second bromodomain (BD2) to facilitate histone H3 lysine 27 trimethylation (H3K27me3) at target gene loci and thereby transcriptional repression. We found that Foxp3 represses transcription of Th2‐specific transcription factor Gata3, while Fbxw7 promotes its ubiquitination‐directed protein degradation. BRD4‐mediated repression of Foxp3 and Fbxw7 in turn promotes BRD4‐ and Gata3‐mediated transcriptional activation of Th2 cytokines including Il4, Il5, and Il13. Chemical inhibition of the BRD4 BD2 induces transcriptional de‐repression of Foxp3 and Fbxw7, and thus transcriptional downregulation of Il4, Il5, and Il13, resulting in inhibition of Th2 cell lineage differentiation. Our study presents a previously unappreciated mechanism of BRD4's role in orchestrating a Th2‐specific transcriptional program that coordinates gene repression and activation, and safeguards cell lineage differentiation. Synopsis: Brd4 interacts with Polycomb repressive complex 2 (PRC2) to repress transcriptional expression of T‐helper 2 (Th2)‐negative regulators Foxp3 and E3‐ubiqutin ligase Fbxw7 during lineage‐specific differentiation of Th2 cells from mouse primary naïve CD4 + T cells. Brd4 promotes Th2 cell differentiation and murine airway inflammation. Brd4 represses a key gene transcriptional program during Th2 cell differentiation. Brd4 recruits PRC2 subunits to repress Th2 negative regulators via H3K27me3. Brd4‐BD2 interacts with the lysine‐acetylated‐EED subunit of PRC2 to promote transcriptional repression. Abstract : BRD4 regulates T‐helper 2 differentiation via the recruitment of PRC2 to promote transcriptional repression of the T‐helper 2‐negative regulators Foxp3 and Fbxw7.